(untitled) (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1982)
The use of chromic oxide for determining dry matter digestibility was estudied; thus it was administered both in gelatin capsules or in the turkeys ration. 45 days old turkeys were randomly divided into four groups, two of which consumed 605 mg of chromicoxide, dayly, the others received it in the ration at 0,17% concentration on dry weigth basis. The faeces were collected during a 24 hour period. The methods, conventional and chromic oxide, were significantly different (P<05), being the calculated alues obtained with the use of indicators systematically smaller than those derived from conventional test. Further, no differences were found between the two ways of chromic oxide administration.